Broken Lutes and Passionate Bodies in A Woman Killed with Kindness - Smid, Deanna (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
Thomas Heywood’s 1607 play, A Woman Killed with Kindness, ends with the protagonist, Frankford, discovering the lute of Anne, the wife he has just banished for adultery. Grieved by the sight of the instrument that he conflates with his marriage and with Anne herself, Frankford exiles the lute along with his wife. When she receives the instrument, Anne plays a lament, then directs her coachman to “go break this lute upon my coach’s wheel, / As the last music that I e’er shall make” (16.69–70). Shortly following the destruction of the lute, Anne dies. Anne’s body and memory, clearly, are inextricably linked to the lute: in the drama, her body is a musical instrument that she can play, that can be played upon, and that can be destroyed. The lute as body metaphor is a common image in early modern English literature, and Heywood both uses and complicates the metaphor. The lute, first, demonstrates Anne’s impossible and paradoxical identity as a chaste wife, noblewoman, and possible prostitute. Moreover, the lute emphasizes Anne’s powerlessness over her own body, particularly her humours. Like other characters in the play, Anne had let her bodily passions control her, but when she breaks the lute, she breaks also her passions’ power over herself and others. Yet when she destroys the lute, she does not abandon music altogether, for music can bring about powerful social harmony. Instead, she plays her own body as a musical instrument, which makes her self-slaughter instructive rather than destructive. Her death is didactic for the audience—both onstage and in the theatre—that gathers around her deathbed, and suggests a variety of means of controlling the passions, some of them more deadly than others. In A Woman Killed with Kindness, Anne’s music is an exemplar of the extraordinary efforts necessary to quell the unruly passions that cause so much of the conflict in the play.